Bisnis Multi Level Marketing dalam Tinjauan Fatwa DSN MUI No: 75/DSN-MUI/VII/2009 (Studi Kasus Pada Member MLM 4Jovem di Situbondo) - Lailatur Rahmah; Wawan Juandi; Muhammad Shaleh (Program Pascasarjana Universitas Ibrahimy, 2017)
One of form economic that develop in this modern era is MLM (Multi Level Marketing) business. One of MLM business that can interest Situbondo society is 4Jovem MLM. This business promise exciting rewads like money, HP, car, umroh, and others. Requirements about Islamic MLM contained in DSN MUI No. 75/DSN-MUI/VII/2009 as one of reference in determining the halal haram of MLM. This research have purpose to present practice 4Jovem MLM business completely and it’s analysis based on Fatwa MUI until the society can take a stand about this 4Jovem MLM. Based on analysis presented, it be concluded that the implementation of the 4Jovem MLM business in Situbondo especially, most of them is have been fulfilled provisions and applied the contract in Fatwa MUI about Syari’ah Direct Sales. However, in the fied practice, there are some 4Jovem practice that have not been fulfilled provisions of Fatwa MUI, that is advanced prerequirement in the Agya reward. For reach that agya car, must recruit of 700 point or members at right and 800 point or members at left. Not only this is gharar in marketing plan, but also 4Jovem practice is ighra’.